Burr formation during drilling of mild steel at different machining conditions. Issue 7 (19th May 2019) - Pramanik, A.; Basak, A. K.; Uddin, M. S.; Shankar, S.; Debnath, S.; Islam, M. N.
ABSTRACT: This paper investigates burr generation while drilling of mild steel grade 350. The influences of feed, speed and point angle on burr height, thrust force, torque and chip ratio are investigated to correlate with burr height. It was found that, the burr height reduces gradually with the rise of speed at minimum feed and point angle. At maximum feed and point angle, initially the height rises with speed and then reduces as speed rises further. The maximum burr is 720 μm at 584 rpm. At maximum point angle and speed, the height rises initially and then reduces as the feed rises where the trend is opposite at minimum feed and speed. The maximum burr is 1223.15 μm at 0.25 mm/rev feed. The variation of burr height with point angle is similar to that with the variation of feed. The maximum burr is 1230 μm at 125°point angle. The trends of thrust forces, torques and chip ration with the variation of different parameters are not similar to that of burr height in most of the cases. The complex interaction between strain hardening and thermal softening plays the main role in burr formation for the considered material.